2017
DOI: 10.1016/j.soard.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of prescribed opioids before and after bariatric surgery: prospective evidence from a U.S. multicenter cohort study

Abstract: Background Limited evidence suggests bariatric surgery may not reduce opioid analgesic use, despite improvements in pain. Objective To determine if use of prescribed opioid analgesics changes in the short- and long-term following bariatric surgery and to identify factors associated with continued and post-surgery initiated use. Setting Ten US hospitals. Methods The Longitudinal Assessment of Bariatric Surgery-2 is an observational cohort study. Assessments were conducted pre-surgery, 6 months post-surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 40 publications
(62 reference statements)
3
52
0
Order By: Relevance
“…Previous studies have shown an unexpected increase in opioid analgesics consumption after bariatric surgery [6][7][8][9]. Our results with a larger population are consistent with their findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown an unexpected increase in opioid analgesics consumption after bariatric surgery [6][7][8][9]. Our results with a larger population are consistent with their findings.…”
Section: Discussionsupporting
confidence: 92%
“…2 approximately 25% of these patients significantly decrease their consumption and the remainder increase it. Mean age among HOCs was significantly lower after surgery ( Table 2); this potentially protective effect has been shown previously [8] but not repeatedly [7], and there are many potentially confounding factors that we in this study are unable to adjust for. The number of HOC individuals in the total population appeared to increase fairly consistently, and if the 3-month period after surgery is excluded, bariatric surgery does not seem to have had an impact on this increase (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This is surprisingly because the massive weight loss, especially in DS, should reduce the patients' musculoskeletal pain. In recent years, there has been a concern about opioid analgesic use among bariatric patients, with 2 studies, 1 from the United States [21] and 1 from Sweden [22], reporting an overall increased use of opioids after bariatric surgery. It is possible that the effect on weight-related pain is overshadowed by the surgical trauma (bariatric operation and subsequent additional procedures) in combination with high prevalence at baseline, 2 important factors predisposing for chronic opioid use [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The risk for malnutrition after RYGB reduces its safety profile. Adverse outcomes related to function and quality of life 139,140 would be reduced if nutrition support of these patients was improved. Therefore, patients, practitioners, and other stakeholders need to know the best practices for the treatment and prevention of nutrition deficiencies.…”
Section: Strategies For Prevention and Treatmentmentioning
confidence: 99%